The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/14656566.2021.1953472
|View full text |Cite
|
Sign up to set email alerts
|

The role of amikacin in the treatment of nontuberculous mycobacterial disease

Abstract: Introduction: Guidelines recommend the use of amikacin in the treatment of nontuberculous mycobacterial (NTM) disease. The authors have evaluated the evidence for the position of amikacin in NTM disease treatment. Areas covered: The authors performed a literature search for original research on amikacin in NTM disease, including its mechanism of action, emergence of resistance, pre-clinical and clinical investigations. Expert opinion: Amikacin shows moderate in vitro activity against the clinically most releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…The NADH dehydrogenase encoded by nuo(A-N) contributes to the proton-motive force in the electron transport chain ( 16 ). Because a proton-motive force is necessary for passive diffusion of molecules into the intracellular space, the decrease in nuo(A-N) expression may also contribute to increased tolerance to aminoglycosides, as their uptake has previously been shown to be dependent on proton-motive force ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NADH dehydrogenase encoded by nuo(A-N) contributes to the proton-motive force in the electron transport chain ( 16 ). Because a proton-motive force is necessary for passive diffusion of molecules into the intracellular space, the decrease in nuo(A-N) expression may also contribute to increased tolerance to aminoglycosides, as their uptake has previously been shown to be dependent on proton-motive force ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, systemic administration of amikacin is limited for prolonged use by the emergence of ototoxicity, vestibular toxicity, and renal toxicity, and the correlation between clinical outcomes and MIC is not well established [ 64 ]. Similarly, systemic penetration of antibiotics to the lung, including amikacin, is limited [ 76 ] requiring increased dosing in order to achieve effective lung concentration [ 77 ], which can lead to an increased risk of serious adverse events [ 78 ]. Many patients cannot safely reach high enough concentrations for optimal efficacy and are at risk of treatment failure [ 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…Acetyltransferase inactivates aminoglycosides and plays a significant role in acquired and intrinsic resistance to these agents in NTM infections similar to other bacteria [ 20 ]. In addition, aminoglycoside phosphotransferases are expressed by some resistant NTM species, including M. fortuitum , M. abscessus , and M. avium [ 62 ]. Nevertheless, some evaluations indicated that resistance by aminoglycoside phosphotransferases is likely to be unusual for most NTM species [ 20 ].…”
Section: Importance Of Antimicrobial Resistance Mechanisms Of Ntm Spe...mentioning
confidence: 99%